Distinguishing Ultrafast Energy Transfer in Atomically Thin MoS2/WS2 Heterostructures. Issue 44 (23rd September 2022) - Zeng, Yan; Dai, Wei; Ma, Rundong; Li, Zhe; Ou, Zhenwei; Wang, Cheng; Yu, Yiling; Zhu, Tong; Liu, Xiaoze; Wang, Ti; Xu, Hongxing
Abstract: Van der Waals semiconducting heterostructures, known as stacks of atomically thin transition‐metal dichalcogenide (TMD) layers, have recently been reported as new quantum materials with fascinating optoelectronic properties and novel functionalities. These discoveries are significantly related to the interfacial carrier dynamics of the excited states. Carrier dynamics have been reported to be predominantly driven by the ultrafast charge transfer (CT) process; however, the energy transfer (ET) process remains elusive. Herein, the ET process in MoS2 /WS2 heterostructures via transient absorption microscopy is reported. By analyzing the ultrafast dynamics using various MoS2 /WS2 interfaces, an ET rate of ≈240 fs is obtain, which is not trivial to the CT process. This study elucidates the role of the ET process in interfacial carrier dynamics and provides guidance for engineering interfaces for optoelectronic and quantum applications of TMD heterostructures. Abstract : The interface carrier transfer process is detected in MoS2 /WS2 heterostructures via transient absorption microscopy. Owing to the weakened interlayer coupling, an energy transfer process with a rate of ≈240 fs is observed in chemical vapor deposition heterostructures. It elucidates the role of the energy transfer process in interfacial carrier dynamics and provides guidance for engineering interfaces for optoelectronic and quantum applications of transition metal dichalcogenide heterostructures.